Assessment of the persistence of anacetrapib and evacetrapib concentrations using two pharmacokinetic modeling approaches. (20th February 2015) - Small, David S.; Ke, Alice Ban; Hall, Stephen D.; Mantlo, Nathan; Rotelli, Matthew; Friedrich, Stuart
Abstract Anacetrapib, a cholesterol ester transfer protein (CETP) inhibitor, has been reported to have longer elimination half‐life after longer treatment. Two pharmacokinetic model‐based approaches were used to assess whether evacetrapib, another CETP inhibitor, could behave similarly. Using population pharmacokinetic (PopPK) modeling, evacetrapib and anacetrapib pharmacokinetics were characterized using available concentration‐time data, and steady‐state conditions were simulated. Published 2‐compartment models for each compound were adapted to include a hypothetical third compartment representing a depot into which drug could partition. Physiologically based pharmacokinetic (PBPK) modeling was used to predict steady‐state conditions and terminal half‐life based on known physicochemical and dispositional properties. The PopPK model described the anacetrapib data well, showing a likely third compartment with estimated apparent volume of 40, 700 L. Anacetrapib's estimated half‐life for this compartment was 550 days. Simulations for evacetrapib using a hypothetical 3‐compartment model, the third compartment being consistent with that of the anacetrapib model, produced predictions inconsistent with reported results, indicating that evacetrapib did not substantially accumulate into a large compartment. The PBPK simulations were consistent with PopPK results, predicting accumulation for anacetrapib (but not evacetrapib) followed by very slow elimination. Based on available data and known physicochemical properties, evacetrapib is not expected to accumulate substantially during long‐term treatment.